Characterization, non-isothermal decomposition kinetics and photocatalytic water splitting of green chemically synthesized polyoxoanions of molybdenum containing phosphorus as hetero atom - D'Cruz, Bessy; Samuel, Jadu; George, Leena (Thermochimica Acta, 2014)
In here, the green synthesis and thermal characterization of a novel polyoxoanions of molybdenum containing phosphorus as hetero atom are reported. The composition and morphology of the nanorods were established by fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetric analysis (TGA) and inductively coupled plasma atomic emission spectroscopic (ICP-AES) techniques. Thermal properties of the nanoparticles were investigated by non-isothermal analysis under nitrogen atmosphere. The values activation energy of each stage of thermal decomposition for all heating rates was calculated by Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunnose (KAS) methods. Invariant kinetic parameter (IKP) method and master plot methodmere also used to evaluate the kinetic parameters and mechanism for the thermal decomposition of cetylpyridinium phosphomolybdate (CPM). Photocatalytic water oxidation mechanism using CPM catalyst in the presence of platinum (Pt) co-catalyst enhances the H-2 evolution and was found to be 1.514 mmol/g/h. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Keggin structure; Master plot method; Polyoxometalate; Water oxidation